2018
DOI: 10.5194/bg-15-2379-2018
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in stream hydrochemistry in responses to typhoon and non-typhoon precipitation

Abstract: Climate change is projected to increase the intensity and frequency of extreme climatic events such as tropical cyclones. However, few studies have examined the responses of hydrochemical processes to climate extremes. To fill this knowledge gap, we compared the relationship between stream discharge and ion input-output budget during typhoon and non-typhoon periods in four subtropical mountain watersheds with different levels of agricultural land cover in northern Taiwan. The results indicated that the high pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…The simulation performed well (KGE = 0.88) and the parameter set (Table S1) was applied to all watersheds, but employing their own climatic inputs and terrain information to simulate their daily streamflow. The annual runoff ratio (estimated streamflow/precipitation) of all the watersheds ranged from 0.70 to 0.80, which was consistent with our previous estimation [5]. The paired weekly ion concentrations and water quantity of precipitation and streamflow were used to calculate the precipitation input, stream water output, and nutrient input-output budgets (stream water output−precipitation input).…”
Section: Precipitation Estimation and Stream Flow Simulationsupporting
confidence: 85%
See 2 more Smart Citations
“…The simulation performed well (KGE = 0.88) and the parameter set (Table S1) was applied to all watersheds, but employing their own climatic inputs and terrain information to simulate their daily streamflow. The annual runoff ratio (estimated streamflow/precipitation) of all the watersheds ranged from 0.70 to 0.80, which was consistent with our previous estimation [5]. The paired weekly ion concentrations and water quantity of precipitation and streamflow were used to calculate the precipitation input, stream water output, and nutrient input-output budgets (stream water output−precipitation input).…”
Section: Precipitation Estimation and Stream Flow Simulationsupporting
confidence: 85%
“…The higher coefficient c of exponent between discharge and Agr Frac presents the magnitude of hydrologic control (Table 3). For NO 3 − export, it is the only ion which necessitates taking the enhancement effect into account (Table 3) [5,45,69]. The higher agricultural land cover could enhance the hydrologic control significantly under the same exponent coefficient, according to Model 4 ( Table 3).…”
Section: Indications From the Nutrient Budgets Estimationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Geochemical tracer data have been analyzed to evaluate groundwater discharges in many rivers (Cook et al, ; Cook et al, ; Cowie et al, ; Gardner et al, ; Gleeson et al, ; Liu et al, ; McCallum et al, ; McDonnell et al, ; A. Smith, Delavau, et al, ; Soulsby et al, ). Understanding water movements between aquifers, hyporheic zones, and stream channels is important in order to improve conceptual and quantitative models of biogeochemical cycling (Brunke & Gonser, ; Dahm et al, ; Barnes et al, ; Cardenas, ; Dawson et al, ; Gomez et al, ; Gomez‐Velez et al, ; Vonk et al, ; Bieroza & Heathwaite, ; Stegen et al, ; Shuai et al, ; Briody et al, ), watershed carbon balances (Barnes et al, ; Boyer et al, , ; Hornberger et al, ; Hotchkiss et al, ; Johnson et al, ; Raymond et al, ; Raymond & Saiers, ; Zimmer & McGlynn, ), chemical weathering (J. Li, et al, ; Rademacher et al, ), stream water quality (Chang, Huang, et al, ; Hyer et al, ), and riparian vegetation density (Jansson et al, ).…”
Section: Groundwater Discharges To Riversmentioning
confidence: 99%
“…Studies at the Hongfeng Lake in Guizhou province, China found that non-point source pollution caused by heavy rainfall results in increasing the total nitrogen content of the lake [40]. Studies in mountain catchments in northern Taiwan found that the hydrochemical processes during typhoon period are significantly different from other times, the high predictability of ion input and output budgets using stream discharge during the non-typhoon period largely disappeared during the typhoon periods [41]. Chiogna et al [42] found that hydrochemical processes are significantly affected by drought.…”
Section: Discussionmentioning
confidence: 99%